Techno-Economic and Life Cycle Assessment of a Small-Scale Integrated Biorefinery for Butyric-Acid Production in Chile - Quintero-Suarez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study evaluates the techno-economic and environmental feasibility of a small-scale biorefinery in Chile’s La Araucanía Region, which utilizes wheat straw as feedstock to produce butyric acid using Clostridium tyrobutyricum. Two scenarios were considered; the standalone wheat straw biorefinery and its integration with the anaerobic digestion of pig manure for biogas production, coupled with a cogeneration system, using the xylo-oligosaccharides and lignin obtained in the pretreatment. The simulations were carried out using Aspen Plus, while the Aspen Process Economic Analyzer was used to perform the economic evaluation. The simulation results were validated with experimental data from the literature. An economic assessment was performed considering the different processes involved. A cradle-to-gate life-cycle analysis (LCA) was also applied to evaluate the different environmental impacts. Both studied scenarios were economically feasible, with the highest butyric acid production cost being USD 2.97/kgbutyricacid; however, this value is still higher compared to corn-based biorefineries. Annexed biogas production increased the costs and was less economically attractive. Nonetheless, the integrations with biogas production had lower environmental impacts, except in the photochemical oxidant formation category, which was higher because of the combustion gases obtained by the cogeneration system. A lower carbon footprint (23.5 kg CO2-eq. per ton of wheat straw) was obtained for the scenario including biogas production. © 2023 by the authors.